Poly(o-aminophenol) film electrodes. Synthesis and characterization. Formation mechanisms. A review article - Tucceri, Ismael Ricardo (2013)
This review, which is divided into three parts, concerns electrochemical synthesis, spectroscopic characterization, and formation mechanisms of poly(o-aminophenol) (POAP) film electrodes. The first part of this review is devoted to describing the electropolymerization process of o-aminophenol (o-AP) on different electrode materials and in different electrolyte media by employing both potentiodynamic and potentiostatic methods. The evolution of the voltammogram during the electrosynthesis of POAP and the assignation of the voltammetric peaks to different species, according to the formation mechanism formulated by each author, are described. The effects of some chemical substances and electrochemical pretreatments of the electrode surface, on the electropolymerization process of o-AP, are also considered in this part of the review. The synthesis of POAP in neutral media, which yields a nonconducting polymer, and its use as component of biosensors and protective layer in corrosion processes, are analyzed at the end of the first part. The second part of this review refers to spectroscopic studies carried out by different authors to both identify the products of the o-AP electro-oxidation and elucidate the chemical structure of POAP film electrodes. This second part of the review also describes the different spectroscopic methods employed to study the redox process of POAP, which allows the demonstration of the existence of transient species during the transition of the completely oxidized form of POAP to the completely reduced one. The third part of this review shows the different mechanisms formulated to interpret the POAP film formation from both acid and basic solutions of o-AP. Also, some electrochemical and spectroscopic data which allowed to propos the corresponding formation mechanisms, especially in basic media, are described.